2014
DOI: 10.1002/pon.3594
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and psychosocial factors mediate exercise effects on sleep quality in breast cancer survivors: pilot randomized controlled trial

Abstract: Objective To improve mechanistic understanding, this pilot randomized controlled trial examined mediators of an exercise intervention effects on sleep in breast cancer survivors (BCS). Methods Forty-six postmenopausal BCS (≤ Stage II, off primary treatment) were randomized to a 3-month exercise intervention or control group. Intervention included 160 minutes/week of moderate intensity aerobic walking, twice weekly resistance training (resistance bands), and six discussion groups (to improve adherence). Blind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 34 publications
(49 reference statements)
3
53
0
1
Order By: Relevance
“…In another study, when compared with controls, the intervention group demonstrated a significant increase in sleep duration with MBSR [18].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In another study, when compared with controls, the intervention group demonstrated a significant increase in sleep duration with MBSR [18].…”
Section: Discussionmentioning
confidence: 91%
“…tance of longitudinal studies because analyzing the patient in 2 or more stages of treatment and documenting the difference in quality of sleep, may be helpful to nurses in managing their patients care. Nine articles reported randomized clinical trials [8,10,[16][17][18][19][20][21]] and 3 were a secondary analysis [4,[22][23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inability of this meta-analysis to detect sleep quality benefits is not unexpected given that currently published randomized controlled trials (RCTs) of aerobic exercise (e.g., home-based walking, supervised aerobic exercise) in breast cancer survivors specifically have not consistently reported beneficial intervention effects on sleep (10,22,27,3032,34,37). In the seven trials measuring self-report, significant intervention effects were reported for overall sleep quality in four studies (two occurred during chemotherapy/radiation) (10,22,27,37), efficiency in one study (during chemotherapy) (10), latency in two studies (one during chemotherapy) (10,31), and sleep duration in one (post-chemotherapy/radiation) (30).…”
Section: Introductionmentioning
confidence: 94%
“…In the seven trials measuring self-report, significant intervention effects were reported for overall sleep quality in four studies (two occurred during chemotherapy/radiation) (10,22,27,37), efficiency in one study (during chemotherapy) (10), latency in two studies (one during chemotherapy) (10,31), and sleep duration in one (post-chemotherapy/radiation) (30). Another post chemotherapy/radiation trial reported beneficial effects on accelerometer measured efficiency, latency, and awake time (34).…”
Section: Introductionmentioning
confidence: 99%